HUBUNGAN STATUS IMUNISASI DAN SIKAP RESPONSIVE FEEDING TERHADAP KEJADIAN STUNTING - Zuhrotunida, Zuhrotunida; Sriyanah, Nour; Wulansari, Meinita; Kartadarma, Supriyatni; Indriani, Ririn (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Stunting in toddlers needs special attention because it can cause inhibition of physical growth, mental development and health status in children. Based on data on the distribution of stunting in the Pekanbaru City District area, it is known that the Limapuluh Community Health Center area has one of the largest numbers of stunting incidents, namely 50 toddlers out of 1,642 toddlers measured.This study aims to determine the determinants of stunting in toddlers in the working area of the Limapuluh Health Center, Pekanbaru City. This study used a quantitative analytic research design with a cross sectional study design. The sampling technique in this study was random sampling, so that the sample in this study was 94 respondents. The measuring tool used was a questionnaire and data analysis used the chi square test. The results of the univariate analysis showed that the immunization history description was mostly complete (51.1%), the status of exclusive breastfeeding was not given (73.4%), then the mother's responsiveness to feeding was in the less category (47.9%). This is consistent with the large number of stunting incidents (67%). The results of the bivariate analysis found that there was a relationship between the completeness of immunization under five and the attitude of responsive feeding of the mother and the incidence of stunting (p-value = 0.000). This study provides suggestions for health workers to make efforts to improve health services through socialization or counseling on the importance of immunization completeness, the process of providing breast milk and food to toddlers in reducing the incidence of stunting.Keywords: Exclusive Breastfeeding, Immunization, Responsive feeding attitude, Stunting Incidents